2020
DOI: 10.1051/0004-6361/202038641
|View full text |Cite
|
Sign up to set email alerts
|

DeGaS-MC: Dense Gas Survey in the Magellanic Clouds

Abstract: Context. Understanding the star-forming processes is key to understanding the evolution of galaxies. Investigating star formation requires precise knowledge of the properties of the dense molecular gas complexes where stars form and a quantification of how they are affected by the physical conditions to which they are exposed. The proximity, low metallicity, and wide range of star formation activity of the Large and Small Magellanic Clouds (LMC and SMC) make them prime laboratories to study how local physical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 112 publications
(145 reference statements)
3
16
0
Order By: Relevance
“…Comparing with the HCN J = 2 → 1 and HCO + J = 2 → 1 data from star-forming clouds of the Magellanic Clouds (Galametz et al 2020), we find that the low-metallicity environment not only slightly deviates the data from the overall surface-density correlations, but also would bias the HCN J = 2 → 1/HCO + J = 2 → 1 line ratio to low ratios. This is consistent with previous findings in low-metallicity galaxies (e.g., Braine et al 2017).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Comparing with the HCN J = 2 → 1 and HCO + J = 2 → 1 data from star-forming clouds of the Magellanic Clouds (Galametz et al 2020), we find that the low-metallicity environment not only slightly deviates the data from the overall surface-density correlations, but also would bias the HCN J = 2 → 1/HCO + J = 2 → 1 line ratio to low ratios. This is consistent with previous findings in low-metallicity galaxies (e.g., Braine et al 2017).…”
Section: Discussionmentioning
confidence: 57%
“…Unfortunately, it is difficult to find systematic observations of the J = 2 → 1 transition towards our Milky Way, while such observations do exist towards the Magellanic Clouds. Therefore, we compare the galaxy survey with the Magellanic Clouds data from Galametz et al (2020), who presented HCN J = 2 → 1 and HCO + J = 2 → 1 observations towards ∼30 LMC and SMC molecular clouds using APEX.…”
Section: Connecting To Star-forming Clouds On Small Scalesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same telescope, Nishimura et al (2016) reported marginal detections of N 2 H + emission in N159W and N113 despite a significant deficit of N-bearing molecules in the LMC (Millar & Herbst 1990). Measurements at millimeter/submillimeter windows (Paron et al 2016;Galametz et al 2020) detected several high-density gas tracers, HCO + , HCN, CS, and (tentative) C 18 O, toward the N159W region. Ott et al (2010) performed an NH 3 survey on such CO prominent regions, including N159W and N113, using the Australia Telescope Compact Array (ATCA).…”
Section: Introductionmentioning
confidence: 99%